142 The Use of Tissue Doppler Imaging and Mitral Annular Plane Systolic Excursion in Addition to Ejection Fraction in Patients Undergoing Breast Cancer Treatment with Trastuzumab. (31st May 2014) - Augustine, Daniel; Sun, Phoebe; Allan, Sarah; Wingfield, Elaine; Wingfield, Elaine; MacIver, David
Abstract : Aims: As part of the care of breast cancer patients considered for trastuzumab, the measurement of LV ejection fraction (EF) pre-treatment is required. Current protocols recommend that EF is then repeated at 3 monthly intervals following the commencement of treatment. We evaluated the use of mitral annular plane systolic excursion (MAPSE) and peak tissue Doppler velocity (Sm) in addition to EF in patients undergoing breast carcinoma treatment with trastuzumab. Methods: 2D echocardiograms (n = 316) were performed by a single operator in 102 patients undergoing trastuzumab therapy. Echocardiograms were performed at baseline (n = 102), 3 mths (n = 83), 6 mths (n = 77), 9 mths (n = 39) and 12 mths (n = 15). A biplane Simpsons derived EF was measured twice and the mean calculated. MAPSE and Sm were measured in 3 consecutive cardiac cycles and the mean of these values used. Paired t-tests were used to express significant changes. Results: Each of the 3 measures of LV systolic function show a significant fall over the 12 mth period (p < 0.05 vs. baseline for all measures – see Table). Absolute values for EF fell by 6.4%, MAPSE by 0.09 cm and Sm by 0.9 cm/s (all p < 0.05). During the study period there were 14 patients (13.7%) whose EF fell by >10%. In five patients (4.9 %) the EF fell within 3 mths (Group 1).In another 9 patients (8.8%) the EF declined only after 6–12 mths (Group 2). For Group 1 the mean reductions in systolic measures were: EF -11.6%, MAPSE -13% and Sm -18%. For Group 2 the changes in systolic measures at 3 mths were less (EF -1.8%; MAPSE-0.1% and Sm -6%). Conclusions: In this observational study, there was a significant reduction in LV systolic function as measured by MAPSE, Sm and EF in patients undergoing trastuzumab therapy over a period of 12 months This apparent cardiotoxicity may be due to a cumulative effect of trastuzumab therapy. The decrease was greatest for Sm compared with MAPSE and EF. The reduction in EF and MAPSE were of similar magnitude. The use of Sm and MAPSE in addition to a standard biplane Simpson's derived EF should be considered for monitoring of systolic function in those patients undergoingtrastuzumab therapy for breast cancer.